Jim Crow Laws and Postcolonial America: Colonial Continuity in August Wilson’s Fences - Sharma Kandel, Bhanu Bhakta (The Outlook: Journal of English Studies, 2025)
The discrimination exercised based on the color of one’s skin is the cornerstone of apartheid, as Nelson Mandela accurately characterized the system as a “crime against humanity”. Every individual is born a social being who can reach his/her fullest development only through interaction with his/her fellows. The denial of any point of this social bond between two individuals brings disintegration with it. A primary symptom of this denial is ‘racial’ prejudice. The problem in human society, even in modern times, is the failure to establish the human ties on the basis of the integrity of individuality of the self, which allows only one alternative: the adoption of attitudes that seek to justify this failure. ‘Racial’ prejudice or the adoption of classified hostilities is one of the methods of trying to satisfy or complete the constellation of needs springing from this failure. In this paper, August Wilson’s play Fences has been dealt with as the primary text, and reviews on the play have been used as the source of data for the purpose. The play has been studied so far as the presentation of hostility between the two races, Whites and Blacks. His emphasis on the need for cultural reclamation, resistance, and psychological liberation offers a powerful framework for analyzing the enduring legacy of segregation and the ongoing fight for racial justice in a so-called postslavery American society. This paper argues that racial prejudice and racial segregation are prevalent even after the declaration of emancipation and civil rights ensured in the constitution in postcolonial America, which hinders the development of humanity to its fullest. The concept of fences built as social barriers is relevant in societies where discrimination is still in practice after the declarations made and legal provisions promulgated against the discrimination that is practiced on the basis of race, caste, gender, or any other form.